Inovasi Media Edukasi: Kipas Cantik Sebagai Alat Meningkatkan Pengetahuan Pasien Diabetes - Wella Juartika; Jhon Feri; Lyara Herniva Yudistira; Syindi Fradila; Tandika Ap Rais (Jurusan Keperawatan, Poltekkes Kemenkes Palembang, 2026)
Background: Diabetes mellitus is a chronic disease that requires continuous education to enable patients to manage their condition independently. One innovative educational medium that can be used is the “educational beauty fan”, which combines health information in an attractive and easy-to-understand format. This study aims to determine the effect of using the educational beauty fan on improving patients’ knowledge about diabetes mellitus. Methods: This study employed a pre-experimental design with a one-group pretest-posttest approach. The sample consisted of 50 diabetes mellitus patients selected using a purposive sampling technique. The intervention involved providing education using the educational beauty fan in a single 30-minute session. Data were collected using a diabetes knowledge questionnaire administered before and after the educational intervention and analyzed using the Wilcoxon Signed Rank Test. Results: The results showed a significant increase in patients’ knowledge levels after the educational intervention using the educational beauty fan (p < 0.05). Before the intervention, most respondents had low knowledge levels (70%), which increased to 86.7% having high knowledge levels after the intervention. The majority of respondents stated that the educational beauty fan helped them understand the information more attractively and memorably. Conclusion: The use of the educational beauty fan is effective in improving patients’ knowledge about diabetes mellitus and can serve as an alternative educational medium in nursing services.